Growth and characterization of boron nitride and carbon nitride thin films - Cometto, Olivier (2018)
This thesis focuses on Boron Nitride (BN) and Carbon Nitride (CN) thin film nanostructuring. Inspired by its carbon counterpart, BN and CN nanocrystal orientation can be tailored to align themselves in the vertical direction. This material “texturing” at the nanoscale opens up opportunities for uncovering new interesting properties in materials, and the synthesis and properties of textured BN and CN is studied in this work. Firstly, a new growth method based on High Power Impulse Magnetron Sputtering (HiPIMS) was created in order to grow BN thin films: A Lanthanum Hexaboride (LaB6) target was reactively sputtered in argon and nitrogen gas. Under specific growth conditions, dependent on temperature and sputtering power density, h-BN nanocrystals with the basal planes aligned in the vertical direction were obtained. The growth mechanism involving the change in alignment to produce vertically ordered BN (voBN) was studied and attributed to the compressive stress applied on the film during growth, where the maximum amount of stress would produce the best alignment. This novel crystalline structure displayed an improvement in thermal conductivity (TC) in the through plane direction by a factor 3 (at 5.1 W.m-1.K-1) compared to a randomly aligned BN film (1.7 W.m-1.K-1), and it was attributed to the vertical texturing, which facilitates the phonon transport in the through film direction. In order to verify the assumption that the phonons move preferentially along the basal planes in the vertical direction, additional thermal characterization was performed using 3 omega, ascertaining an anisotropy in thermal transport with an in plane TC of 0.26 W.m-1.K-1, while the through plane TC was found to be 16 times greater at 4.26 W.m-1.K-1. Molecular Dynamics (MD) simulations were used to successfully re-enact the TC anisotropy observed experimentally, attributing the difference to the many interfaces between crystalline and amorphous regions and the preferential phonon propagation along the vertically ordered crystalline basal planes. COMSOL Multiphysics simulations were used to quantify the performance of voBN at preventing heat cross talk, allowing an increase by a factor of 4 in hot spot density compared to SiO2, without inducing any temperature increase. Finally, some carbon and CN thin films with different nanostructuring were studied. Transient Grating Spectroscopy (TGS) was used to study the Surface Acoustic Waves (SAW) decay in the films, and deduce the thermal diffusivity of the substrate-thin film pair. Pure carbon films, together with CN films were produced with amorphous and vertically ordered structure in order to study the effect of nanostructure on the thermal diffusivity. Vertically ordered CN exhibited an enhanced thermal diffusivity response compared to a-CN with a greater value by a factor 3. It was deduced that this increase is mostly driven by the difference in nanostructuring. In addition, it was shown that the nitrogen content in the film plays a key role in the thermal diffusivity value, and it is assumed that its presence in a film decreases the atomic ordering, thus impeding the phonon transport.